Solid-state 13C NMR analysis of size and density fractions of marine sediments: Insight into organic carbon sources and preservation mechanisms - Dickens, A. F.; Baldock, J. A.; Smernik, R. J.; Wakeham, S. G.; Arnarson, T. S.; Gelinas, Y.; Hedges, J. I. (Geochimica et Cosmochimica Acta, 2006)
id: 1702

A Critical Evaluation of Interlaboratory Data on Total, Elemental, and Isotopic Carbon in the Carbonaceous Particle Reference Material, NIST SRM 1649a - Currie, L. A.; Benner, B. A., Jr.; Kessler, J. D.; Klinedinst, D. B.; Klouda, G. A.; Marolf, J. V.; Slater, J. F.; Wise, S. A.; Cachier, H.; Cary, R.; Chow, J. C.; Watson, J.; et al. (J Res Natl Inst Stand Technol, 2002)
Because of increased interest in the marine and atmospheric sciences in elemental carbon (EC), or black carbon (BC) or soot carbon (SC), and because of the difficulties in analyzing or even defining this pervasive component of particulate carbon, it has become quite important to have appropriate reference materials for intercomparison and quality control. The NIST "urban dust" Standard Reference Material((R)) SRM 1649a is useful in this respect, in part because it comprises a considerable array of inorganic and organic species, and because it exhibits a large degree of ((14)C) isotopic heterogeneity, with biomass carbon source contributions ranging from about 2 % (essentially fossil aliphatic fraction) to about 32 % (polar fraction). A primary purpose of this report is to provide documentation for the new isotopic and chemical particulate carbon data for the most recent (31 Jan. 2001) SRM 1649a Certificate of Analysis. Supporting this is a critical review of underlying international intercomparison data and methodologies, provided by 18 teams of analytical experts from 11 institutions. Key results of the intercomparison are: (1) a new, Certified Value for total carbon (TC) in SRM 1649a; (2) (14)C Reference Values for total carbon and a number of organic species, including for the first time 8 individual PAHs; and (3) elemental carbon (EC) Information Values derived from 13 analytical methods applied to this component. Results for elemental carbon, which comprised a special focus of the intercomparison, were quite diverse, reflecting the confounding of methodological-matrix artifacts, and methods that tended to probe more or less refractory regions of this universal, but ill-defined product of incomplete combustion. Availability of both chemical and (14)C speciation data for SRM 1649a holds great promise for improved analytical insight through comparative analysis (e.g., fossil/biomass partition in EC compared to PAH), and through application of the principle of isotopic mass balance.
Currie, L ABenner, B A JrKessler, J DKlinedinst, D BKlouda, G AMarolf, J VSlater, J FWise, S ACachier, HCary, RChow, J CWatson, JDruffel, E R MMasiello, C AEglinton, T IPearson, AReddy, C MGustafsson, OQuinn, J GHartmann, P CHedges, J IPrentice, K MKirchstetter, T WNovakow, TPuxbaum, HSchmid, Heng2002/01/01 00:00J Res Natl Inst Stand Technol. 2002 Jun 1;107(3):279-98. doi: 10.6028/jres.107.022. Print 2002 May-Jun.

Sedimentary organic matter preservation: A test for selective degradation under oxic conditions - Hedges, J. I.; Hu, F. S.; Devol, A. H.; Hartnett, H. E.; Tsamakis, E.; Keil, R. G. (American Journal of Science, 1999)
We report here a test of the hypothesis that the extent of organic matter preservation in continental margin sediments is controlled by the average period accumulating particles reside in oxic porewater immediately beneath the water/sediment interface. Oxygen penetration depths, organic element compositions, and mineral surface areas were determined for 16 sediment cores collected along an offshore transect across the Washington continental shelf, slope, and adjacent Cascadia Basin. Individual amino acid, sugar, and pollen distributions were analyzed for a 11 to 12 cm horizon from each core, and (14)C-based sediment accumulation rates and stable carbon isotope compositions were determined from depth profiles within a subset of six cores from representative sites. Sediment accumulation rates decreased, and dissolved O(2) penetration depths increased offshore along the sampling transect. As a result, oxygen exposure times (OET) increased seaward from decades (mid-shelf and upper slope) to more than a thousand years (outer Cascadia Basin). Organic contents and compositions were essentially constant within individual sediment cores but varied consistently with location. In particular, organic carbon/surface area ratios decreased progressively offshore and with increasing OET. Three independent compositional parameters demonstrated that the remnant organic matter in farther offshore sediments is more degraded. Both concentration and compositional patterns indicated that sedimentary organic matter exhibits a distinct and reproducible "oxic effect" OET helps integrate and explain organic matter preservation in accumulating continental margin sediments and hence provides a useful tool for assessing transfer of organic matter from the biosphere to the geosphere.
263rmTimes Cited:194Cited References Count:104

Influence of oxygen exposure time on organic carbon preservation in continental margin sediments - Hartnett, H. E.; Keil, R. G.; Hedges, J. I.; Devol, A. H. (Nature, 1998)
Today, over 90% of all organic carbon burial in the ocean occurs in continental margin sediments(1). This burial is intrinsically linked to the cycling of biogeochemically important elements (such as N, P, S, Fe and Mn) and, on geological timescales, largely controls the oxygen content of the atmosphere(2-4). Currently there is a volatile debate over which processes govern sedimentary organic carbon preservation(5-8). In spite of numerous studies demonstrating empirical relationships between organic carbon burial and such factors as primary productivity(9), the flux of organic carbon through the water column(10), sedimentation rate(11,12), organic carbon degradation rate(13), and bottom-water oxygen concentration(8,14), the mechanisms directly controlling sedimentary organic carbon preservation remain unclear. Furthermore, as organic carbon burial is the process that, along with pyrite burial(15), balances O-2 concentrations in the atmosphere, it is desirable that any mechanism proposed to control organic carbon preservation include a feedback buffering atmospheric oxygen concentrations over geological time. Here we compare analyses of sediments underlying two regions of the eastern North Pacific Ocean, one which has oxygen-depleted bottom waters and one with typical oxygen distributions. Organic carbon burial efficiency is strongly correlated with the length of time accumulating particles are exposed to molecular oxygen in sediment pore waters. Oxygen exposure time effectively incorporates other proposed environmental variables(8-14), and may exert a direct control on sedimentary organic carbon preservation and atmospheric oxygen concentrations.
Yv594Times Cited:355Cited References Count:27